PEMBUBARAN BADAN USAHA MILIK NEGARA BERBENTUK PERSEROAN TERBATAS (BUMN PERSERO): Jimmy Simanjuntak - Simanjuntak, Jimmy (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
In accordance with Article 1 number 1 of Law Number 19 of 2003 on State-Owned Enterprises, the definition of State-Owned Enterprises (SOE) are business entities whose capital is entirely or mainly owned by the state through direct participation that is derived from the state’s separated assets. In the implementation of business sector in Indonesia, SOE in several business sectors has made a major contribution to national economic development. There are, however, performance gap of SOE in several business sectors, which leads to the liquidation of SOE that are unable to compete. But, the liquidation process of SOE is more complicated compared to the liquidation process of private company. This research aims to provide an in-depth analysis of the liquidation process of SOE.